Use of a Side Deposit to Increase Consumption in Children with Food Refusal. (23rd April 2015) - Rubio, Emily K.; Borrero, Carrie S. W.; Taylor, Tessa
<x xml:space="preserve">Abstract</x> Research has shown that nonremoval of the spoon and physical guidance procedures can be effective in treating active food refusal (e.g., head turning and spoon pushing) and increasing food consumption. These procedures alone may not be effective in treating more passive food refusal (e.g., sitting still without opening mouth). We defined and evaluated the use of a side deposit procedure using a reversal design. Results showed that this procedure, when added to a treatment package including other components (e.g., nonremoval of the spoon and physical guidance), was effective in increasing food consumption and treating passive food refusal. Copyright © 2015 John Wiley & Sons, Ltd.